Liriomyza commelinae (Diptera: Agromyzidae): an alternative host for parasitoids of the leafminer pest Liriomyza huidobrensis - Fenoglio, Maria Silvina (2009)
The potential of Liriomyza commelinae (Frost) (Diptera: Agromyzidae) as an alternative host for parasitoids of the pest leafminer Liriomyza huidobrensis (Blanchard) was investigated. We particularly focussed on the specific composition of the parasitoid complex and its impact on L. commelinae, frequency of associations, dependency of parasitism on host density and additive effects of species richness on total parasitism. Mined leaves of Commelina erecta (Commelinaceae) were collected from different localities of Co´rdoba province (Argentina) from 1991 to 1994, and also from different sites of Co´rdoba city. In total, 25 species of parasitoids (Hymenoptera) were associated with L. commelinae, of which 13 were shared with L. huidobrensis. Chrysocharis flacilla and Diglyphus websteri (Eulophidae) were the most abundant parasitoid species on L. commelinae, the former being the most frequently associated with the leafminer. Total parasitism, averaging 50%, did not depend on parasitoid species richness. No significant relationship was found between parasitism caused by the main species and host abundance. The potential for using the system C. erecta–L. commelinae in the conservation biological control of L. huidobrensis is discussed.